PENERAPAN PRINSIP HAM PADA SISTEM LAYANAN DAN RUJUKAN TERPADU (SLRT) DI KABUPATEN BANDUNG - Anjani, Firda Dwi; Rusyidi, Binahayati; Fedryansyah, Muhammad (Social Welfare Study Program, 2023)
Abstract. The implementation of SLRT must seek the application of legal, responsive, transparent, participatory, gender equality, accountable, objective, and sustainable principles. Bandung Regency is an area that has held SLRT since 2016 until now and has received Best Practice achievements from the Ministry of Social Affairs. In fact, the characteristics of the region can be a challenge for the implementation of the SLRT implementation principle. Namely, the male population is greater than the female population, the area is large and consists of lowlands and highlands, and the 69 OPDs have their own programs and target recipients. The researcher wants to know how the Bandung Regency SLRT applies the principles of its implementation by using a human rights-based approach theory. This is because there is harmony between the principles of implementing SLRT and human rights principles in the form of participation, accountability, non-discrimination and equity. Information regarding the implementation of SLRT Bandung Regency is presented using qualitative data, sourced from interviews, non-participant observation, and literature studies. The findings of the study state that the implementation of SLRT in Bandung Regency shows active community participation and differences in treatment in the delivery of services that support substantive gender equality. On the other hand, not all OPDs in Bandung Regency have succeeded in integrating their programs and program beneficiary targets with SLRT. Thus, service delivery is not fully sustainable. However, this is not a form of government reluctance, but rather due to limited resources. Keywords: Implementation of SLRT; Human Rights-Based Approach; Human Rights Principle. Abstrak. Penyelenggaraan SLRT harus mengupayakan penerapan asas legal, responsif, transparan, partisipatif, kesetaraan gender, akuntabel, objektif, dan berkelanjutan. Kabupaten Bandung merupakan daerah yang telah menyelenggarakan SLRT sejak tahun 2016 hingga saat ini dan mendapatkan prestasi Best Practice dari Kementerian Sosial. Padahal, karakteristik wilayahnya dapat menjadi tantangan diterapkannya asas penyelenggaraan SLRT. Yaitu, jumlah penduduk laki-laki yang lebih banyak dibandingkan perempuan, wilayah yang luas dan terdiri atas dataran rendah dan tinggi, serta 69 OPD yang memiliki program dan sasaran penerimanya masing-masing. Peneliti ingin mengetahui bagaimana SLRT Kabupaten Bandung menerapkan asas penyelenggaraannya dengan menggunakan teori pendekatan berbasis HAM. Pasalnya, terdapat keselarasan antara asas penyelenggaraan SLRT dengan prinsip HAM berupa partisipasi, akuntabilitas, non diskriminasi dan ekuitas. Informasi mengenai penyelenggaraan SLRT Kabupaten Bandung disajikan menggunakan data kualitatif, bersumber dari kegiatan wawancara, observasi non partisipan, dan studi literatur. Hasil temuan penelitian menyatakan penyelenggaraan SLRT Kabupaten Bandung menunjukkan upaya partisipasi aktif masyarakat dan perbedaan perlakuan dalam penyelenggaraan layanan yang mendukung kesetaraan substantif gender. Di sisi lain, belum semua OPD di Kabupaten Bandung berhasil mengintegrasikan program dan sasaran penerima programnya dengan SLRT. Sehingga, penyelenggaraan layanan belum sepenuhnya berkelanjutan. Namun, hal tersebut bukan merupakan bentuk keengganan pemerintah, melainkan karena keterbatasan sumber daya. Kata kunci: Penyelenggaraan SLRT; Pendekatan Berbasis HAM; Prinsip HAM